Perencanaan Strategis Public Relations Biker Jowo Depok dalam Mempertahankan Brand Image - Saputro, Maulana Setyo; Sumarni, Lilik (Dialogika : Jurnal Penelitian Komunikasi dan Sosialisasi, 2025)
Motorcycle communities not only function as a platform for hobbies but also as a medium for shaping identity and image within society. In this context, the role of Public Relations is crucial in maintaining reputation and building positive relationships with the public. A strong brand image helps the community sustain its existence while countering the negative stigma often associated with motorcycle groups. This study aims to explore and analyze the Public Relations planning of Biker Jowo Depok in maintaining its brand image, using the RPACE model (Research, Planning, Action and Communication, Evaluation) by Cutlip & Center (2017). The theoretical framework of this research refers to the concept of Public Relations planning by Cutlip & Center. The method used is qualitative descriptive, with data collection techniques including in-depth interviews, secondary data from the website and Instagram, as well as documentation. Data validity was tested through source triangulation involving the public and community members. The results show that Biker Jowo Depok implements all four dimensions of Public Relations planning according to the RPACE model. The community utilizes social media and various offline activities to build a positive image based on Javanese cultural values, such as togetherness (guyub), social awareness (tanggap), and cultural preservation (nguri-uri). Evaluation is carried out periodically through social media engagement analysis and feedback from members. The main challenges faced include negative stereotypes toward motorcycle communities and competition with other groups. However, through adaptive and collaborative Public Relations strategies, Biker Jowo Depok has succeeded in maintaining its image as a professional, culturally-rooted, and socially conscious community.